DUREN GELIS (Posbindu Remaja untuk Generasi Milenial Sehat) sebagai Langkah Deteksi dan Pengendalian Penyakit Tidak Menular pada Remaja Usia Sekolah - Pertiwi, Kartika Dian; Sswanto, Yuliaji; Sofiyanti, Ida (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
Current health burden shows a shift in trends from communicable diseases to increasing non-communicable diseases (NCD). Therefore it is very important if health services are directed to promotive and preventive efforts, such as through health promotion. Teen Health Survey results show increasing obesity disorders, smoking cases, symptoms of diabetes mellitus and hypertension among students. At present, the risk of noncommunicable diseases has already affected young people of school age. Noting this condition, the formation of Posbindu Non-Communicable Diseases (PTM) in schools is considered to be a solution as a step to detect and control PTM risk factors in adolescents. Community service activities DUREN GELIS (Posbindu Adolescent for Healthy Millennial Generation) as a Detection and Control of Non-Communicable Diseases in School Age Adolescents aims to reduce the number of non-communicable diseases in adolescents through early detection of the risk of non-communicable diseases. This activity begins with the preparation phase to obtain an overview of the partners' health conditions followed by the transfer of knowledge related to non-communicable diseases and the postbindu in stages I and II. In stage 2 an initiation or formation of a school health cadre of 23 students was carried out, followed by an early PTM risk detection skills training activity using several medical devices. This activity takes place from January to April 2020. Community service activities DUREN GELIS (Posbindu Adolescent for Healthy Millennial Generation) as a Detection and Control of Non-Communicable Diseases in School Age Adolescents has a positive influence on students' knowledge of non-communicable and posbindu diseases, things this is evidenced by the increase in the number of students in the good knowledge category and the sustainability of the program implementation for partners which is held once a month every Friday the first weekABSTRAK Beban kesehatan pada saat ini menunjukkan adanya pergeseran tren dari penyakit menular menjadi meningkatnya penyakit tidak menular atau non-communicable diseases (NCD). Maka dari itu sangat penting jika pelayanan kesehatan diarahkan ke upaya-upaya promotif dan preventif, seperti lewat promosi kesehatan. Hasil Survei Kesehatan Remaja menunjukkan makin meningkatnya gangguan obesitas, kasus merokok, gejala diabetes mellitus serta hipertensi dikalangan pelajar. Saat ini, resiko penyakit tidak menular sudah menyerang kaum remaja usia sekolah. Memperhatikan kondisi seperti ini, pembentukan Posbindu Penyakit Tidak Menular (PTM) di sekolah dirasa dapat menjadi solusi sebagai langkah deteksi dan pengendalian faktor risiko PTM pada remaja. Kegiatan pengambdian kepada masyarakat DUREN GELIS (Posbindu Remaja untuk Generasi Milenial Sehat) sebagai Langkah Deteksi dan Pengendalian Penyakit Tidak Menular pada Remaja Usia Sekolah bertujuan untuk menurunkan angka penyakit tidak meular pada remaja melalui deteksi dini risiko penyakit tidak menular. Kegiatan ini diawali dengan tahap persiapan untuk memperoleh gambaran kondisi kesehatan mitra dilanjutkan dengan transfer knowledge terkait penyakit tidak menular dan posbindu pada kegiatan tahap I dan II. Pada tahap 2 juga dilakukan inisiasi atau pembentukan kader kesehatan sekolah yang berjumlah 23 orang siswa, kemudian dilanjutkan dengan kegiatan pelatihan keterampilan deteksi dini risiko PTM mempergunakan beberapa alkes. Kegiatan ini berlansung dari bulan januari hingga april 2020. Kegiatan pengabdian kepada masyarakat DUREN GELIS (Posbindu Remaja untuk Generasi Milenial Sehat) sebagai Langkah Deteksi dan Pengendalian Penyakit Tidak Menular pada Remaja Usia Sekolah memberikan pengaruh positif pada pengetahuan siswa terhadap penyakit tidak menular dan posbindu, hal ini terbukti dengan peningkatan jumlah siswa dengan kategori pengetahuan baik dan keberlanjutan pelaksanaan program pada mitra yang dilaksanakan sebulan sekali setiap hari jumat minggu pertama.